2021
DOI: 10.3389/fmats.2021.677642
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Monitoring of Bolt Looseness Using Multichannel Piezoelectric Active Sensing and CBAM-Based Convolutional Neural Network

Abstract: The bolted connection is widely utilized in engineering to practically and rigidly couple structural components. The integrity of the connection is paramount to the safety of the structure and has prompted the development of many monitoring methods, including the piezoelectricity-based active sensing method. However, the active sensing method cannot quantify bolt looseness due to the unclear relationship between bolt looseness and the single monitoring index typically used in the active sensing method. Thus, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…They concluded that the CNN model trained using the scalograms obtained from the updated FE model accurately predicted the damage state of the structure. Chen et al 155 combined a 1D CNN model with a multichannel active sensing method to determine bolt looseness in three steel-bolted joint specimens. They divided their approach into four steps: (i) data acquisition, (ii) data preprocessing, (iii) model training and validation, and (iv) bolt looseness monitoring.…”
Section: Mechanical Properties Ofmentioning
confidence: 99%
“…They concluded that the CNN model trained using the scalograms obtained from the updated FE model accurately predicted the damage state of the structure. Chen et al 155 combined a 1D CNN model with a multichannel active sensing method to determine bolt looseness in three steel-bolted joint specimens. They divided their approach into four steps: (i) data acquisition, (ii) data preprocessing, (iii) model training and validation, and (iv) bolt looseness monitoring.…”
Section: Mechanical Properties Ofmentioning
confidence: 99%
“…From the perspective of the model, CBAM is better in capturing the intrinsic correlation between features. The classification performance of the network is effectively improved by locally focusing observation of the signal to be studied [45].…”
Section: Cbammentioning
confidence: 99%
“…During the service life of a bolted structure, the torque can evolve according to operational conditions such as loading, in particular when these structures are submitted to vibrations. Monitoring the loosening condition in bolted structures during operation remains challenging because contact and friction in bolted joints induce a nonlinear stochastic behavior [16][17][18][19][20][21]. A common solution consists of measuring the pretightening force using a strain gauge bonded on the top surface of a bolt head [22].…”
Section: Ae Signals Clusteringmentioning
confidence: 99%